SIGNIFIKANSI INFORMASI ISU KEBOCORAN DATA PRIVASI TOKOPEDIA TERHADAP PERILAKU FANDOM : Studi Eksplanatif Terhadap Khalayak Pengguna - Azziza Ratri Pradina (2022)
This research is motivated by the case of user privacy data leakage experienced by Tokopedia in 2020. Data leaks that occur can cause losses to various parties, including the company and customers. This study aims to see the effect of quality information related to the case of user data leakage experienced by Tokopedia on the behavior of the audience studied using attribution theory. The method used in this study is a quantitative explanation with the aim of explaining the causal relationship between variables. Data leakage information is measured based on the quality value it has and consists of 4 characteristics, namely accurate (accuracy), timely (timeless), relevant (relevancy), and complete (complete). In contrast, audience behavior is measured using attribution theory based on internal and external factors, which pays attention to the principle of consensus, the principle of consistency, and the principle of distinctiveness. The results of this study explain that Ha is accepted and H0 is rejected so that quality information about Tokopedia user data leakage affects audience behavior. Information regarding the leakage of Tokopedia user data received by the public is of good quality and the behavior shown by the audience is influenced by internal factors. The conclusion of this study explains that there is an influence between quality information related to the leakage of Tokopedia user data and the behavior of the audience with a value of 0.341 which is a low level of relationship. The higher the quality of information, the higher the audience's behavior.